SEDAYU DISTRICT FARMERS’ MOTIVATION ON INTRODUCTION RATS CONTROLLING TECHNOLOGY USING OWL - Mukti Ahmad Nurcahya (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
The pest control technology is currently developed in the world of agriculture to ensure better yields. The development of pest control technology has led to restoring the balance of the natural rice fields ecosystem. Sedayu district has rats attack problem that requires an immediate solution to restore rice production. Rat controlling technology with owls was reintroduced as an effort to control rats. A total of 60 farmers measured the level of motivation to find out how high the motivation of the farmers in the introduction of pest control technology for rodents and owls. The level of motivation of farmers was examined using the proportion test that found that more than 50% of the farmers had high motivation, besides that, the level of motivation on the aspects of existence, relatedness and growth was also measured to determine the level of motivation of farmers in each of these aspects.